1 PENGELOLAAN OBYEK WISATA TAMAN MARGASATWA MANGKANG KOTA SEMARANG - Lutfi Isnan Santiko; Sri Suwitri; Susi Sulandari (Journal of Public Policy and Management Review, 2013)
The tourism sector is currently one of the leading sectors for the Government of the Republic of Indonesia in the country's foreign exchange earning. To increase the number of tourist visits to Indonesia, especially to the Central Java this Program as part of an effort to increase the number of tourist visits to the Provinces of Central Java and also improve the welfare of society through the development and management of the tourism sector. Yet at a visit to taman margasatwa showed the need for improvement the management of Taman Margasatwa Mangkang. The aim of this research is described the conduct of a management tourist attractions Taman Margasatwatwa Mangkang to advance of tourism potential that exists in the city of semarang and described constraints that have been is in the management of Taman Margasatwa Mangkang the city of Semarang. The kind of research using qualitative descriptive approach with interviews and observation. The number of subjects research is 4 respondent This research result showed the management Taman Margasatwa Mangkang not optimal indicated by the road that there is damage, condition enclosure poorly groomed, sdm who have not sufficient, and there has been authorized LK. Structure that has been set at uptd taman margasatwa city semarang not optimal due to the position in this structure that is occupied by employee inappropriate with skills. Condition about current visit is good enough because increase every year and only decline in 2010. Facilities and infrastructure in Taman Margasatwa Mangkang is quite feasible, but its treatment that are lacking. Capability of productivity employees UPTD Taman Margasatwa still less than optimal,. Because of employees less diligent in carrying out their duties. Whose leadership doing in Taman Margasatwa is usually made of staff as a partner of is not merely subordinate. In accomplishment of an objective is found in tourism, market competition lack of promotion in taman margasatwa and infrastructure that has not been able to closely follow the developments.